PANDANGAN DA'I KONTEMPORER INDONESIA TERHADAP PERHITUNGAN WETON DALAM PENENTUAN PASANGAN: ANALISIS ETNOGRAFI VIRTUAL DI MEDIA TIKTOK - Maydani Nur Majidah; Ahmad Fauzi (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
This study analyzes the views of four contemporary Indonesian preachers, that is Hanan Attaki, Buya Yahya, Gus Baha, and Ustadz Abdul Somad regarding the practice of Weton calculation and parental blessing in marital decision-making as presented on TikTok. Using a qualitative approach through content analysis and virtual ethnography, the research examined four TikTok sermons (10-15 minutes each) uploaded between January 2023 and December 2024, along with audience interactions in the comment sections. The findings reveal that all preachers reject Weton as a determinant of marriage compatibility because it contradicts Islamic monotheism, yet they differ in their preaching approaches: Hanan Attaki and Gus Baha emphasize rational faith, Buya Yahya adopts a moderate stance that tolerates cultural expressions, while Ustadz Abdul Somad firmly condemns superstition. The study shows that TikTok serves as a space for negotiating religious and cultural values, with Buya Yahya's moderate approach being the most accepted. This research contributes to contemporary digital da'wah studies by highlighting the emergence of new religious authority within Indonesia's digital landscape.